2021
DOI: 10.1155/2021/6657597
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Long Noncoding RNA Lx8-SINE B2 as a Marker of Pluripotency

Abstract: Pluripotency and self-renewal of embryonic stem cells (ESCs) are marked by core transcription regulators such as Oct4, Sox2, and Nanog. Another important marker of pluripotency is the long noncoding RNA (lncRNA). Here, we ind that a novel long noncoding RNA (lncRNA) Lx8-SINE B2 is a marker of pluripotency. LncRNA Lx8-SINE B2 is enriched in ESCs and downregulated during ESC differentiation. By rapid amplification of cDNA ends, we identified the full-length sequence of lncRNA Lx8-SINE B2. We further showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Many lncRNAs derived from transposable element (TE), such as retrotransposon HERVH derived lncRNA, also act as important pluripotency regulators in ESCs [34,35]. Chen et al found that lncRNA Lx8-SINE B2, which has overlapping exon1 and 3 with neighboring transposon LINE1 family Lx8 and SINE B2 in genome and contains a long intergenic non-coding RNA (lincRNA) lincRNA-1282, is highly abundant in ESCs and a marker of pluripotent mESCs [35]. Its expression is downregulated during ESC differentiation or when cultured in serum containing medium, but is upregulated in 2i containing medium [35].…”
Section: Long Noncoding Rnas Interact With Core Pluripotency Factors ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Many lncRNAs derived from transposable element (TE), such as retrotransposon HERVH derived lncRNA, also act as important pluripotency regulators in ESCs [34,35]. Chen et al found that lncRNA Lx8-SINE B2, which has overlapping exon1 and 3 with neighboring transposon LINE1 family Lx8 and SINE B2 in genome and contains a long intergenic non-coding RNA (lincRNA) lincRNA-1282, is highly abundant in ESCs and a marker of pluripotent mESCs [35]. Its expression is downregulated during ESC differentiation or when cultured in serum containing medium, but is upregulated in 2i containing medium [35].…”
Section: Long Noncoding Rnas Interact With Core Pluripotency Factors ...mentioning
confidence: 99%
“…Chen et al found that lncRNA Lx8-SINE B2, which has overlapping exon1 and 3 with neighboring transposon LINE1 family Lx8 and SINE B2 in genome and contains a long intergenic non-coding RNA (lincRNA) lincRNA-1282, is highly abundant in ESCs and a marker of pluripotent mESCs [35]. Its expression is downregulated during ESC differentiation or when cultured in serum containing medium, but is upregulated in 2i containing medium [35]. They further showed that core pluripotency regulators OCT4 and SOX2 directly bind to a TE ORR1D2 in promoter region of lncRNA Lx8-SINE B2, activating its expression in mESCs, which is functionally important for the expression of another key pluripotency factor c-MYC [35].…”
Section: Long Noncoding Rnas Interact With Core Pluripotency Factors ...mentioning
confidence: 99%
“…Notably, RLTR13D6 and RLTR9 are bound by key pluripotency factors (Nanog and Oct4) and serve as enhancers to govern gene expression in mouse ESCs ( Sundaram et al., 2017 ; Todd et al., 2019 ). An ORR1D2 locus that is bound by Oct4 and Sox2 can serve as a promoter to drive the expression of a retrotransposon-derived lncRNA, Lx8-SINE B2 , which is critical for ESC metabolism ( Chen et al., 2021b , 2022 ). In mouse oocytes, intronic MTC drives the expression of the Dicer isoform ( Flemr et al., 2013 ).…”
Section: Expression and Functions Of Ervs In Mouse Escs And Early Emb...mentioning
confidence: 99%
“…All samples were examined in triplicates. Primer sequences for qPCR analysis are listed in Additional file 1: Table S1, some of which have been described previously [20,34,35].…”
Section: Rna Extraction Reverse Transcription and Quantitative Pcr (Q...mentioning
confidence: 99%